PERLINDUNGAN HUKUM TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DALAM MEMPEROLEH PENDIDIKAN (Studi Lembaga Pemasyarakatan Kelas IIA Anak Tanjung Gusta Medan) - Ramli Tambunan; Madiasa Ablisar; Mahmud Mulyadi; Edy Ikhsan (Universitas Sumatera Utara, 2015)
ABSTRACT Children protection activity is a good law so it can guarantee the law action brought as a result of the law protection and can protect bad activity in education for Children's who have law processing in Institute Pemasyakatan Class IIA Tanjung Gusta Medan. From the research results are known, Concepts Setting Legal Protection Against Children in conflict with the Law In Getting Education Right in the penitentiary setting about the rights of child prisoners in obtaining education while in the correctional Institution; Implementation of the Protection of Rights of Children's Education Law Granting Dilapas Tanjung Gusta Kids IIA Class field has not gone well with the results of the study 37% of schools implemented formal education provision MTsN-3 field by virtue of a collective agreement, 83% of spiritual education and vocational education has not been effective by 174 children taken prisoner as much as 10% of the total population; Constraints Giving Child Rights Education Class IIA Tanjung Gusta Medan started from legislation that is not set out clearly in the form of education for the criminal, and the lack of facilities to support the educational process skills. Keywords: Legal Protection, Children in conflict with law, Penitentiary.